Maid from the Philippines isang manwal para sa domestic workers sa Hong Kong, Singapore at Malaysia - Sta. Maria, Amparita S. (Makati city Ateneo Human Rights Center, 1998)
A comprehensive handbook for Filipino domestic helpers in Hong Kong, Singapore and Malaysia. It is a guide on how they can protect their immigrant rights and how their needs as overseas workers can be responded.
Purpose: A handbook that provides a "significant and effective guide for workers in their work. An effective way of response to the ODWs' needs. Provides realistic situations of ODWs in other countries and offers solutions in helping them abroad.
Contents: Things to know before going abroad. Background of Hong Kong, Singapore, and Malaysia. Organizations abroad. Rules and regulations of each country. Support groups for ODWs. References.
Keywords: Women domestics -- Hongkong -- Handbooks, manuals, etc; Women domestics -- Malaysia -- Handbooks, manuals, etc; Women domestics -- Singapore -- Handbooks, manuals, etc; Filipino women -- Employment -- Foreign countries